Tanggung Jawab Perusahaan terhadap Hak Pekerja dalam Pemutusan Hubungan Kerja akibat Kepailitan - I Nengah Sucipta Angga Putra; I Gusti Ayu Eviani Yuliantari; Putu Eva Ditayani Antari; Kadek Januarsa Adi Sudharma (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the legal protection of workers' rights during Termination of Employment (PHK) due to company bankruptcy, as well as assessing the conformity between applicable legal provisions and practice in the field. The method used is normative legal research with a statutory and factual approach. The research examines various legal regulations related to employment and bankruptcy, as well as the implementation of these regulations in resolving employment disputes. The research results show that the regulation of layoffs according to Law Number 6 of 2023 concerning Job Creation emphasizes that layoffs are the termination of the employment relationship due to certain things which result in the end of the rights and obligations between workers and employers which is a last resort. In practice, however, workers often experience difficulties in obtaining their normative rights, especially when companies face financial instability or insolvency. Then the responsibilities that can be carried out by companies to realize fair legal protection for workers are divided into 2 (two) efforts, namely preventive and repressive. Preventive efforts include compliance with labor regulations and transparent communication, while repressive efforts are carried out through dispute settlement and fulfillment of workers’ compensation rights. This research confirms the existence of a gap between legal norms and practice in the field. Therefore, it is necessary to increase legal awareness and strengthen regulatory enforcement to ensure the fulfillment of the rights of workers affected by layoffs.